Immunogenicity of monkeypox virus surface proteins and cross-reactive antibody responses in vaccinated and infected individuals: implications for vaccine and therapeutic development - Jing Liu; Xun Wang; Yiting Zhang; Changyi Liu; Meng Zhang; Chen Li; Peiling Liu; Shanshan Li; Kaifeng Wei; Yiming Cai; Hongjie Yu; Zhiliang Hu; et al. (Infectious Diseases of Poverty)
Abstract Background The monkeypox virus (MPXV) has raised global health concerns due to its widespread transmission. This study evaluated the MPXV immunogenic antigens and the impact of vaccinia virus (VACV) vaccination and MPXV infection on cross-reactive antibody responses to conserved proteins from representative MPXV strains that reflected the evolutionary trajectory. Methods Phylogenetic analyses were first conducted to reveal the evolutionary trajectory of MPXV from 1970 to 2024. A total of 84 serum samples were collected: 42 from VACV-vaccinated individuals, 12 from MPXV-infected participants in the early stage, 13 from the late stage, and 17 from naive individuals. Demographic data, MPXV and HIV status, as well as other clinical information were collected using standardized forms. Immunogenicity, cross-reactive antibody responses, and amino acid similarity to 15 MPXV surface proteins were assessed using enzyme-linked immunosorbent assays, VACV neutralization tests, and sequence alignment. Data analysis methods included analysis of variance, Mann–Whitney U test, binary logistic regression, Pearson correlation, and linear regression, with a significance threshold of P < 0.05. Results The 186 complete genome sequences were classified into different clades and lineages, ranging from clade Ia to clade IIb C.1.1. Individuals infected with MPXV demonstrated strong antibody responses to antigens A35R, B6R, H3L, and E8L. VACV-vaccinated individuals exhibited broader cross-reactivity, particularly against A21L (P = 0.0003), A28L (P = 0.0028), A29L (P = 0.0324), G2R (P = 0.0003), and H2R (P = 0.0008), compared to MPXV-infected individuals. Pearson correlation analysis revealed significant associations (P = 0.0049) between antibody responses and the amino acid sequence similarity with other orthopoxviruses. Furthermore, MPXV-infected individuals exhibited greater neutralizing activity against VACV than those VACV-vaccinated individuals (P < 0.0001), while the vaccinated group retained cross-protective immunity even decades post-vaccination. Conclusions A35R, B6R, H3L, and E8L are the main immunogenic antigens of MPXV. VACV-vaccination triggers a cross-reactive antibody response to MPXV surface proteins. Our findings suggest the need for targeted vaccines and antibody treatments for MPXV, as well as the reintroduction of smallpox vaccinations with booster doses for high-risk groups. Graphical Abstract